Wpływ polityki kredytowej na wartość portfela kredytowego banków komercyjnych - Ivanova, Nadezda (The Impact of the Credit Policy on the Value of the Credit Portfolio of Commercial Banks, 2005)
In this article questions related to the impact of credit policy on the value of the credit portfolio through the objective financial reporting in the Estonian banks are tackled. From 2003 in all Estonian commercial banks (as well as in other institutions), accounting for financial instruments including credit claims follows the Accounting Standards, which mainly comply with International Financial Reporting Standards (IAS 32, IAS 39, IAS 21). According to the new regulation, all the financial instruments should be accounted at their cost, which is the fair value, indicated best by the market value i.e the market price. As to credit claim, the exceptionality of the fair value principles should be respected, because the market value of bank's credit generally does not exists. Therefore the first registration in the accounting system should follow the present value. Nominal - i.e according to sum paid out - credits are accounted for only if the nominal (or fixed in the contract) interest rate and the average market interest rates are equal for credits with analogous conditions and risks. In case these interest rates are different, the first recognition in the accounting system should be with their present value or using the discounted future cash flows generated from the claim. Further accounting of the credit claim is based on the corrected cost method, meaning that the initial cost of the claim should be corrected with accumulated depreciation of the difference between the nominal and present value, the repayment of the principal of the claim, allowance or possible mark down due to the uncollectibility (in case of the uncollectible credits). The difference between the nominal and the present value of the credit claim is set to the nominal level in the financial reports by annual crediting of the interests costs or debiting of the interest benefits by effective interest rate that differs from interest rate in the agreement. Doing this, the International Financial Reporting Standard is fulfilled by which financial instruments are accounted by their fair value in the situation where financial instruments including credit claims do not have a market value. Corrected present value method is based on the time value of money that was up to now widely used only in finances but which is actually used in accounting as well. Rationally managing their credit policy, banks manage their credit portfolio value. Refining the credit policy improves the credit portfolio quality and increases its value. The use of the new credit claim accounting methods, despite of its complexity, enables to account for the changes in crediting in the Financial Reports more objective than before. This improves comparability of banks crediting result, not only inside the country, but also internationally, as well as possibilities of understanding banks competition advantages and deficiencies.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 36-45